A gender gap in primary and secondary heart dysfunctions in systemic sclerosis: a EUSTAR prospective study. Issue 1 (23rd October 2014) - Elhai, Muriel; Avouac, Jérôme; Walker, Ulrich A; Matucci-Cerinic, Marco; Riemekasten, Gabriela; Airò, Paolo; Hachulla, Eric; Valentini, Gabriele; Carreira, Patricia E; Cozzi, Franco; Balbir Gurman, Alexandra; Braun-Moscovici, Yolanda; et al.
Abstract : Objectives: In agreement with other autoimmune diseases, systemic sclerosis (SSc) is associated with a strong sex bias. However, unlike lupus, the effects of sex on disease phenotype and prognosis are poorly known. Therefore, we aimed to determine sex effects on outcomes. Method: We performed a prospective observational study using the latest 2013 data extract from the EULAR scleroderma trials and research (EUSTAR) cohort. We looked at (i) sex influence on disease characteristics at baseline and (ii) then focused on patients with at least 2 years of follow-up to estimate the effects of sex on disease progression and survival. Results: 9182 patients with SSc were available (1321 men) for the baseline analyses. In multivariate analysis, male sex was independently associated with a higher risk of diffuse cutaneous subtype (OR: 1.68, (1.45 to 1.94); p<0.001), a higher frequency of digital ulcers (OR: 1.28 (1.11 to 1.47); p<0.001) and pulmonary hypertension (OR: 3.01 (1.47 to 6.20); p<0.003). In the longitudinal analysis (n=4499), after a mean follow-up of 4.9 (±2.7) years, male sex was predictive of new onset of pulmonary hypertension (HR: 2.66 (1.32 to 5.36); p=0.006) and heart failure (HR: 2.22 (1.06 to 4.63); p=0.035). 908 deaths were recorded, male sex predicted deaths of all origins (HR: 1.48 (1.19 to 1.84); p<0.001), but did not significantly account for SSc-related deaths. Conclusions: Although more common in women, SSc appears as strikingly more severe in men. Our results obtained through the largest worldwide database demonstrate a higher risk of severe cardiovascular involvement in men. These results raise the point of including sex in the management and the decision-making process.